Airway Foreign Bodies in Patients that Underwent Bronchoscopies with General Anesthesia in Dr. Soetomo General Academic Hospital Surabaya - Sabrina, Annisa Maya; Maulydia; Perdana, Rizka Fathoni; Fitriati, Mariza (Indonesian Journal of Anesthesiology and Reanimation, 2022)
Introduction: Airway foreign body (AFBs) is the most common emergency for ENT-HN (Ear, Nose, Throat-Head Neck) that requires immediate treatment. The gold standard management for AFBs is a bronchoscopy performed under general anesthesia (GA). Objective: This study aims to determine the profile of AFBs patients who underwent bronchoscopies with GA at Dr. Soetomo General Hospital Surabaya from January 2018 – December 2019. Materials: This is a descriptive, retrospective study that uses data from medical records. Microsoft Excel was used to analyze the data. 22 patients met the inclusion criteria. Results: The most common ages were 11 to 20-year-olds (73%), 55% were female, and 45% were male. The patients were from outside (73%) and inside (27%) Surabaya. As much as 67% of the sampled patients had coughs and 23% were symptomless. The foreign bodies found were pins (67%), clipboard nails (14%), and nuts (9%). These AFBs were located in the left main bronchus (45%), trachea (32%), and right main bronchus (18%), and in 5% of these cases, the AFBs could not be located. The duration between the event and the bronchoscopy was mostly less than 1 day (54%), 2 days (32%), and 3 days (14%). Most cases (90%) were without AFBs complications, but some had obstruction (5%), and hemoptysis (5%). Most patients also had an uncomplicated bronchoscopy (81%), however, some suffered lesions (14%) and bleeding (5%). A majority of the patients were also ASA I (68%), and the remainder were classified as ASA II (18%), and III (14%). The premedication drugs administered were fentanyl (41%), and a combination of fentanyl and midazolam (41%). Meanwhile, the most frequently maintained anesthetic agent was Isoflurane+O2 (27%). Most patients also did not have any comorbid factors (85%), but some had anemia (5%), obstruction (5%), as well as obesity followed by sputum retention and hypernatremia (5%). Conclusion: Most AFB patients who underwent bronchoscopy under GA were 11-20 years old, female, and had a cough as a clinical symptom. Most AFBs were pins at the left main bronchus. The duration between the incident and the bronchoscopy was less than 1 day. There were also mostly no complications of AFBs and bronchoscopies. The most common physical status in patients was ASA I, with fentanyl only or fentanyl and midazolam as a premedication drug. The most common agent used to maintain the anesthesia was a combination of isoflurane and O2. Most patients also had no comorbid factors for GA.